PSYCHOPHYSIOLOGICAL CHARACTERISTICS OF WOMEN IN DEPENDENCE ON THE OVARIOHORMONAL CYCLE PHASE AND PROGESTERONE ACTIVITY (PART 1) - K. B. Muravlyova; O. I. Kuzminova; S. E. Petrova; M. V. Skoraya; O. M. Bazanova (Бюллетень сибирской медицины, 2013)
With the aim to identify the effects of menstrual cycle phase on the cognitive and psycho-emotional characteristics in 78 women aged 18–27 years were studied in a within-subject design Half the subjects began during their follicular phase and half began during their luteal phase (LP). The level of psycho-emotional tension was lowest, but cognitive performance efficiency is a highest in LP that is associated with the highest saliva progesterone level.